2005
DOI: 10.1152/japplphysiol.00315.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous exercise acutely changes platelet and B-lymphocyte CD39 expression

Abstract: . Vigorous exercise acutely changes platelet and B-lymphocyte CD39 expression. J Appl Physiol 98: 1414 -1419, 2005; doi:10.1152/japplphysiol.00315.2004.-CD39/ATP diphosphohydrolase is expressed on B lymphocytes, cytotoxic T lymphocytes, monocytes, platelets, and endothelial cells, and it has a critical role in the inhibition of platelet responsiveness. To determine whether strenuous exercise could acutely change expression of CD39 in platelets and lymphocytes, eight healthy sedentary men, 34 yr old (SD 7), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
22
2
Order By: Relevance
“…Variation of the ADPase:ATPase ratio has been observed between individuals, although intra-personal variation has not yet been observed. Although very low levels of CD39 expression on platelets has been reported [23,24], our laboratory found no difference between ATPase and ADPase activity in platelet-rich and platelet-poor plasma. This suggests that the contribution of platelet CD39 is minimal to non-existent and that leukocyte and endothelial cell CD39 exert primary control of ATP and ADP conversion to ADP and AMP (unpublished data).…”
Section: Introductioncontrasting
confidence: 63%
“…Variation of the ADPase:ATPase ratio has been observed between individuals, although intra-personal variation has not yet been observed. Although very low levels of CD39 expression on platelets has been reported [23,24], our laboratory found no difference between ATPase and ADPase activity in platelet-rich and platelet-poor plasma. This suggests that the contribution of platelet CD39 is minimal to non-existent and that leukocyte and endothelial cell CD39 exert primary control of ATP and ADP conversion to ADP and AMP (unpublished data).…”
Section: Introductioncontrasting
confidence: 63%
“…6), although the basal NTPDase was higher than in trained athletes. Probably, the thromboregulatory role of soluble NTPDase is even more relevant for patient populations who display the increased platelet aggregability at rest and especially during exercise, and in addition suffer from endothelial dysfunction and insufficient release of antiplatelet compounds (El‐Sayed, 2002; Coppola et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among cellular elements of the blood, the leucocytes, but not erythrocytes and platelets, contribute to the catabolism of nucleotides (Coade & Pearson, 1989; Heptinstall et al 2005). Notably, flow cytometric analysis of venous blood from physically active men showed moderate exercise‐mediated increase in CD39 expression on B‐lymphocytes (from 46 ± 11 to 59 ± 11%, respectively) (Coppola et al 2005). Vascular NTPDase can be diminished under conditions of inflammation or oxidant stress, thereby causing profound shifts in vascular permeability and local procoagulant responses (Robson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, increased platelet aggregation in response to exercise was observed by light transmission aggregometry without [ 11 , 15 , 29 32 ] and after adjustment of platelet count in platelet-rich plasma (PRP) [ 21 , 33 , 34 ], but also with other techniques including electrical impedance aggregometry [ 13 , 35 41 ], filtragometry [ 42 44 ], calculation of reduction of single (unaggregated) platelets after agonist stimulation [ 45 50 ], and platelet aggregation after application of shear stress by a rotational viscometer [ 20 , 51 , 52 ]. Notably, this observed increase of in vitro platelet aggregation after acute exercise is not in contrast to those studies that found no effects of exercise on GPIIb/IIIa activation, as platelet aggregation rather depends on sensitivity of platelets towards agonists than on the basal activation state of glycoprotein IIb/IIIa.…”
Section: Influence Of Acute Exercise On Diverse Aspects Of Platelementioning
confidence: 99%
“…The influence of acute exercise on the expression of P-selectin on platelets has been addressed by several studies and yielded contradictory results. Basal P-selectin expression (i.e., without intentional platelet stimulation applied ex vivo) has been found to be increased [ 17 , 42 , 44 , 64 68 ] after acute exercise, although this was not in all studies statistically significant [ 13 , 18 , 21 ]. Notably, several studies found no influence of exercise on basal P-selectin expression [ 11 , 19 , 22 , 69 71 ].…”
Section: Influence Of Acute Exercise On Diverse Aspects Of Platelementioning
confidence: 99%